If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(n + -2) + 5n = 2(-3n + 4) + -2n + 1 Reorder the terms: -3(-2 + n) + 5n = 2(-3n + 4) + -2n + 1 (-2 * -3 + n * -3) + 5n = 2(-3n + 4) + -2n + 1 (6 + -3n) + 5n = 2(-3n + 4) + -2n + 1 Combine like terms: -3n + 5n = 2n 6 + 2n = 2(-3n + 4) + -2n + 1 Reorder the terms: 6 + 2n = 2(4 + -3n) + -2n + 1 6 + 2n = (4 * 2 + -3n * 2) + -2n + 1 6 + 2n = (8 + -6n) + -2n + 1 Reorder the terms: 6 + 2n = 8 + 1 + -6n + -2n Combine like terms: 8 + 1 = 9 6 + 2n = 9 + -6n + -2n Combine like terms: -6n + -2n = -8n 6 + 2n = 9 + -8n Solving 6 + 2n = 9 + -8n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '8n' to each side of the equation. 6 + 2n + 8n = 9 + -8n + 8n Combine like terms: 2n + 8n = 10n 6 + 10n = 9 + -8n + 8n Combine like terms: -8n + 8n = 0 6 + 10n = 9 + 0 6 + 10n = 9 Add '-6' to each side of the equation. 6 + -6 + 10n = 9 + -6 Combine like terms: 6 + -6 = 0 0 + 10n = 9 + -6 10n = 9 + -6 Combine like terms: 9 + -6 = 3 10n = 3 Divide each side by '10'. n = 0.3 Simplifying n = 0.3
| 7x-3+5x+3=180 | | 4(3x-5)+6=2x-14 | | 24=-4m | | 7x-3+5x+3=90 | | 2x-6=52 | | 13=(5-8m) | | -9(4x-6)=27 | | -4(4-3m)=-52 | | 16n^2-36= | | -17=5n-20 | | -(6x+(4x+3))=7-(5x+6) | | px-qr=-r | | 3(x-1)+8=-10 | | 2*3*4x-2*3*5x=6 | | 2=4c-2 | | 6n-20+5n=2(n+4)+4n-35 | | 6m=3m+36 | | 625=25g-105 | | -3=-2/3(x+2) | | (p^2-16)(p^2-3p-4)=0 | | 6m^2-18m-16= | | 9-4m=3 | | 155x=(120)(155)+120x | | 3x=7x+30 | | 5c-4-2c+1=10c+2 | | 145x=(120)(145)+120x | | 10-8z=2(5-4z) | | X+19=120 | | 7(x+7)-34= | | 150x=(125)(150)+125x | | 5t+8r=11 | | 145x=(125)(145)+125x |